NEW STUDENTS’ EXPECTATIONS OF ISLAMIC RELIGIOUS EDUCATION AS THE ETHICAL FOUNDATION FOR ECONOMICS AND BUSINESS IN THE ERA OF INDUSTRY 4.0 - Haryadi Jaka Susila (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2026)
Islamic Religious Education plays a crucial role in fostering students’ moral character, ethical awareness, and professional integrity in higher education. However, limited empirical studies have examined how Moral Foundations, Economic Ethics, and Business Ethics collectively shape students’ expectations of PAI, particularly among economics and business students in the context of Industry 4.0. This study aims to analyze the influence of Moral Foundations, Economic Ethics, and Business Ethics on students’ expectations of PAI in the digital era. The study employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and involved 105 first-semester students of STIE Balikpapan as respondents. This study offers a novel perspective by integrating Moral Foundations, Economic Ethics, and Business Ethics into a single analytical model to explain students’ expectations of PAI. The results indicate that Economic Ethics and Business Ethics have positive and significant effects on students’ expectations of PAI, whereas Moral Foundations do not demonstrate a significant influence. These findings suggest that students perceive PAI as more relevant when it emphasizes the practical application of Islamic economic and business values rather than general moral principles alone. The study contributes to the literature on Islamic Religious Education by highlighting the importance of contextual and discipline-based ethical dimensions in shaping students’ expectations. Therefore, PAI learning should integrate Islamic economic ethics, business ethics, and contemporary digital issues to enhance its relevance, strengthen professional character, and prepare students to address ethical challenges in the digital economy.